Coal Fly Ash Characterization from Cement Industry â€œXâ€ as an Initial Study in Its Utilization - Farrah Fadhillah Hanum; Aster Rahayu; Ulung Muhammad Sutopo; Zahrul Mufrodi (Universitas Ahmad Dahlan, 2020)
The discharge of fly ash from the coal combustion process has become a matter of concern over the last few decades. Most of the fly ash will be disposed of in the landfill. This disposal gives a negative impact on the environment through the heavy metal contained in fly ash. Coal fly ash characterization is needed to be done to get proper information about coal fly ash before it could be utilized. In this research, coal fly ash characterization from one of cement industry in Indonesia has been done by a qualitative and quantitative method. This research carried out some instrumentation such as Scanning Electron Microscopy (SEM), X-ray fluorescence spectrometer (XRF) and SEM â€“ Electron Dispersive X-ray spectroscopy (SEM-EDX) to analyze the coal fly ash sample. The result showed that the main component in this coal ash sample is SiO2, Al2O3, Fe2O3, CaO, and MgO. This information will be used as an initial study in coal fly ashes utilization research in the next research.